Incidence of Timely Outpatient Follow-Up Care After Emergency Department Encounters for Acute Heart Failure. Issue 9 (8th September 2022) - Kilaru, Austin S.; Illenberger, Nicholas; Meisel, Zachary F.; Groeneveld, Peter W.; Liu, Manqing; Mondal, Angira; Mitra, Nandita; Merchant, Raina M.
Abstract : Background: Patients who are discharged from the emergency department (ED) after an encounter for acute heart failure are at high risk for return hospitalization. These patients may benefit from timely outpatient follow-up care to reassess volume status, adjust medications, and reinforce self-care strategies. This study examines the incidence of outpatient follow-up care after ED encounters for acute heart failure and describes patient characteristics associated with obtaining timely follow-up care. Methods: We conducted a retrospective cohort study using an administrative claims database for a large US commercial insurer, from January 1, 2012 to June 30, 2019. Participants included adult patients discharged from the ED with principal diagnosis of acute heart failure. The primary outcome was obtaining an in-person outpatient clinic visit for heart failure within 30 days. We also examined the competing risk of all-cause hospitalization within 30 days and without an intervening outpatient clinic visit. We estimated competing risk regression models to identify patient characteristics associated with obtaining outpatient follow-up and report cause-specific hazard ratios. Results: The cohort included 52 732 patients, with mean age of 73.9 years (95% CI, 73.8–74.0) and 27 395 (52.0% [95% CI, 51.5–52.4]) female patients. Within 30 days of the ED encounter, 12 279 (23.2%) patients attended an outpatient clinic visit for heart failure, with 8382 (15.9%) patients hospitalized before they could obtain an outpatient clinic visit. In the adjusted analysis, patients that were younger, women, reporting non-Hispanic Black race, and had fewer previous clinic visits were less likely to obtain outpatient follow-up care. Conclusions: Few patients obtain timely outpatient follow-up after ED visits for heart failure, although nearly 20% require hospitalization within 30 days. Improved transitions following discharge from the ED may represent an opportunity to improve outcomes for patients with acute heart failure.